Link between Impulsivity and Overeating: Psychological and Neurobiological Perspectives - Deniz Atalayer (Psikiyatride Güncel Yaklaşımlar, 2018)
In most basic terms impulsivity is defined as a tendency to act without control. Impulsivity has been implicated in the onset, symptomatic expression, and maintenance of overeating. Specifically, high impulsivity and associated poor inhibitory control, along with sensation seeking and reward sensitivity, as well as negative affect have been found to have an interaction effect on emotional eating, which may lead to binge eating and obesity. Moreover, associations between overeating and impulsive behaviors such as difficulty in response inhibition, planning, attention, addiction, or risk taking etc. have been previously shown. The purpose of this review is to summarize the evidence from psychology regarding the potential role of the impulsivity trait in overeating, with implications on the treatments for obesity and binge eating.